2016
DOI: 10.18869/acadpub.ismj.19.3.398
|View full text |Cite
|
Sign up to set email alerts
|

Effect of evidence-based Medical Education on knowledge and ability to use and apply it among clinical students of Bushehr University of Medical Sciences: a controlled trial

Abstract: Background: Evidence Based Medicine is the ability of physicians to use and integrate the best clinical evidence based in accordance with patient's condition, that this evidence have obtained from reliable clinical trials and without bias. In recent years To improve the clinical care quality provided to patients, physicians clinical experience have been combined with research evidence of similar clinical case. The aim of this study was to determine the effect of short-term implementation of evidence-based medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…The lowest posttest scores were in the domain of biostatistics; this may be due to unfamiliarity of medical students with these concepts. The same results were observed in our previous study (7,14).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The lowest posttest scores were in the domain of biostatistics; this may be due to unfamiliarity of medical students with these concepts. The same results were observed in our previous study (7,14).…”
Section: Discussionsupporting
confidence: 92%
“…Other studies showed the positive effects of EBM education on students' knowledge (5,7,9). The results of posttest scores based on the EBM domains revealed that the best result is obtained in teaching PICO, which is due to the fact that clinical cases for EBM teaching are straightforward and clearly talk about the 4 constituents of the PICO questions.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations